Tourism Carrying Capacity of Coastal Ecosystems on Ketawai Island, Central Bangka, Indonesia - Sujadi Priyansah; Erny Poedjirahajoe; Lies Rahayu Wijayanti Faida (Talenta Publisher, 2026)
Ecotourism development, especially in Central Bangka Island of Ketawai more rapidly. The rapid tourist activities on the Island of Ketawai can cause loss of quality attractions for damage to the ecosystem. This is because the pressure on the environment caused by the increased number of tourists. This study aims to determine the maximum capacity rating with ratings of three aspects: (1) the carrying capacity of the region (DDK), (2) the carrying capacity of the environment (the carrying capacity of the physical / PCC and the carrying capacity of the real / RCC), and (3) ecological carrying capacity (AR). This study uses primary data by direct observation in the field and secondary data from relevant agencies. An assessment of the carrying capacity of the region (DDK), an assessment of the carrying capacity of the environment using methods the Physical Carrying Capacity (PCC), the carrying capacity of the Real (RCC), and an assessment of the ecological carrying capacity (AR). The results obtained, there are two tourist activity on the island of Ketawai are picnic and camping. The result of the carrying capacity of the region (DDK) for picnic activities is 240 people / day and camping activities is 900 people/day. The results of the physical carrying capacity (PCC) for picnic activities is 249 people / day and for camping is 100 people / day. Assessment of the real carrying capacity (RCC) for picnic activities is 239 people / day and camping 96/day. Ecological carrying capacity assessment. (AR) obtained the results of 81 people / day for a picnic and activity type 43 / day for camping activities. The value of these calculations are still well above the actual number of tourists who currently account for 9 person / day. Attraction Development Ketawai Island can still be optimized however, by taking into account the balance and sustainability of the local environment.